Lab on a chip for a low-carbon future. Issue 5 (15th February 2023) - Datta, Sujit S.; Battiato, Ilenia; Fernø, Martin A.; Juanes, Ruben; Parsa, Shima; Prigiobbe, Valentina; Santanach-Carreras, Enric; Song, Wen; Biswal, Sibani Lisa; Sinton, David
Abstract : We describe how lab-on-a-chip systems can help address challenges in: (I) carbon sequestration, (II) hydrogen storage, (III) geothermal energy extraction, (IV) bioenergy, (V) recovering critical materials, and (VI) water filtration and remediation. Abstract : Transitioning our society to a sustainable future, with low or net-zero carbon emissions to the atmosphere, will require a wide-spread transformation of energy and environmental technologies. In this perspective article, we describe how lab-on-a-chip (LoC) systems can help address this challenge by providing insight into the fundamental physical and geochemical processes underlying new technologies critical to this transition, and developing the new processes and materials required. We focus on six areas: (I) subsurface carbon sequestration, (II) subsurface hydrogen storage, (III) geothermal energy extraction, (IV) bioenergy, (V) recovering critical materials, and (VI) water filtration and remediation. We hope to engage the LoC community in the many opportunities within the transition ahead, and highlight the potential of LoC approaches to the broader community of researchers, industry experts, and policy makers working toward a low-carbon future.